Research of prospects of involving pharmacists in ukraine to help patients trying to quit smoking - Shuvanova, Оlena; Rohulia, Olha; Malyi, Volodymyr; Piven, Olena; Chehrynets, Anna (ScienceRise: Pharmaceutical Science, 2023)
The aim. The study aimed to determine the prevalence of tobacco smoking among pharmacy workers in Ukraine, their awareness of the harmfulness of certain types of cigarettes, the attitude of pharmacy managers and pharmacists towards their colleagues’ smoking, as well as the ability of pharmacists to provide effective help in smoking cessation and assessment of prospects for the participation of pharmacists in tobacco smoking control programs if such programs are to be implemented in Ukraine. Materials and methods. The survey involved 239 employees of Ukrainian pharmacies under the age of 30 working in different regions. According to the geographical structure, the respondents represent 22 regions of Ukraine. Results. The experience of countries where active assistance to those who want to quit smoking pharmacists are involved suggests that pharmacists' support can help increase adherence to smoking cessation drugs and provide additional behavioural support as an adjunct to pharmacotherapy, which is quite effective. Currently, there are no such programs in Ukraine. The survey results show that Ukrainian pharmacists under the age of 30 are aware of the dangers of smoking. Most of them assess the level of their training in smoking cessation assistance as sufficient, but they only mean advice on the use of drugs in smoking cessation. Conclusions. Thus, in order to introduce the services of active support by pharmacists for people trying to quit smoking in Ukraine, it is required to create the necessary conditions for the interest of pharmacies and pharmacists in carrying out this type of activity and the implementation of programs of additional training in methods of active support for people trying to quit smoking